Modification of TIMI Score as a Predictive Model for 30-Day Mortality in Young STEMI Patients - M. Tasrif Mansur; Muhammad Yamin; Lusiani Rusdi; Murdani Abdullah; Birry Karim; C. Martin Rumende; Maruhum Bonar H. Marbun; Hamzah Shatri (Jurnal Penyakit Dalam Indonesia)
Introduction. Cardiovascular disease is a leading cause of death worldwide. Three-quarters of these deaths occur in lowand middle-income countries among individuals in their productive years. ST-segment elevation myocardial infarction (STEMI) is a dangerous manifestation of coronary artery disease (CAD) and can lead to sudden death. Smoking and a family history of early CAD are major risk factors for STEMI cases. However, their role in any risk stratification system for patients has not been clearly established. The most widely used score in assessing the prognosis of STEMI patients is the TIMI score, but its accuracy in the young patient population is still unknown. The objectives of this study were to determine the proportion of mortality in young STEMI patients at RSCM, validate the TIMI score in young patients, and develop a risk stratification system for young STEMI patients.